A Multi-Parameter Fusion Turning Force Prediction Method Considering the Arc Radius of the Tool Tip. Issue 2 (October 2020) - Gou, Jianfeng; Zhang, Guangpeng
Abstract: According to the force analysis of turning, the principle of oblique cutting is applied. A new multi-parameter fusion turning force prediction method considering the radius of cutter tip arc is proposed. The mathematical model of new turning force prediction is established. The influence of cutting parameters, cutting parameters and machining conditions on the cutting force is considered in this method. By using the method of cutting force coefficient of the front cutting face, three cutting force coefficients on the front cutting face can be solved by one turning experiment, and the turning force prediction can be realized under the conditions of different cutting tool geometry parameters and different cutting parameters. Finally, the feasibility of the method is verified by TC4 turning test of titanium alloy. And it has high prediction accuracy.